Adenosine A(2A) receptor-mediated facilitation of noradrenaline release involves protein kinase C activation and attenuation of presynaptic inhibitory receptor-mediated effects in the rat vas deferens - Queiroz, G (2003)
In the epididymal portion of rat vas deferens, facilitation of noradrenaline release mediated by adenosine A(2A) receptors, but not that mediated by beta(2)-adrenoceptors or by direct activation of adenylyl cyclase, was attenuated by blockade of alpha(2)-adrenoceptors and abolished by simultaneous blockade of alpha(2)-adrenoceptors, adenosine A(1) and P2Y receptors. The adenosine A(2A) receptor-mediated facilitation was not changed by inhibitors of protein kinase A, protein kinase G or calmodulin kinase II but was prevented by inhibition of protein kinase C with chelerythrine or bisindolylmaleimide XI. Activation of protein kinase C with phorbol 12-myristate 13-acetate caused a facilitation of noradrenaline release that was abolished by bisindolylmaleimide XI and reduced by antagonists of alpha(2)-adrenoceptors, adenosine A(1) and P2Y receptors. Activation of adenosine A(2A) receptors attenuated the inhibition of noradrenaline release mediated by the presynaptic inhibitory receptors. This effect was mimicked by phorbol 12-myristate 13-acetate and prevented by bisindolylmaleimide XI. It is concluded that adenosine A(2A) receptors facilitate noradrenaline release by a mechanism that involves a protein kinase C-mediated attenuation of effects mediated by presynaptic inhibitory receptors, namely alpha(2)-adrenoceptors, adenosine A(1) and P2Y receptors.